2018
DOI: 10.3390/f9110720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thinning on the Spatial Structure of a Larix gmelinii Rupr. Secondary Forest in the Greater Khingan Mountains

Abstract: Thinning is an important way to adjust and optimize the spatial structure of forests. The study of its impacts support a better understanding of the succession process of secondary forests after interference. To study the changes in forest spatial structure under different thinning intensities and stand densities, we considered five thinning intensities including unthinned (0%), low (3.4%, 6.2%, 12.5%), medium (16.8%, 20.9%, 25.5%), high (34.4%, 40.0%, 47.9%), and extra-high (50.6%, 59.9%, 67.3%) intensity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The uniform angle index (W), mingling (M) and dominance (U) of each stand were calculated using the information shown in Table 2 [8]. To avoid edge effects, a buffer of 1m was set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uniform angle index (W), mingling (M) and dominance (U) of each stand were calculated using the information shown in Table 2 [8]. To avoid edge effects, a buffer of 1m was set.…”
Section: Discussionmentioning
confidence: 99%
“…soil erosion and lower quality of harvested timber [6]. The potential for human intervention to improve the stand status of forests is a source of controversy [7,8]. Some researchers have found that forest planning provides many environmental benefits, and assists in making management decisions to improve the future state of forests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the spatial distribution pattern of a plant population is closely related to the biological characteristics of the plant species itself [58,59], including the diversity characteristics of a plant population and community, life history strategies, regeneration and reproduction patterns, intermediate and intraspecific competition, and inter-clonal trade-off. On the other hand, the spatial distribution pattern of a population is also deeply affected by external environmental factors [60,61], including the soil temperature, humidity, salinity, nutrition, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary forests have been reported to sequester carbon at higher rates through faster growth [19]. However, a study gives the opposite view that secondary forests have low productivity, low carbon sequestration rate and low soil fertility, which seriously restrict and affect the sustainable development of the forest [20]. This means that completely transforming the stand structure through natural renewal would be a long process.…”
Section: Introductionmentioning
confidence: 99%